Direct-current stimulation does little to improve the outcome of working-memory training in older adults - Nilsson, Jonna (Psychol Sci, 2017)
The promise of transcranial direct current stimulation (tDCS) as a modulator of cognition has appealed to researchers, media, and general public. Researchers have suggested that tDCS may increase effects of cognitive training. We report results from a study (n=123; age=65-75 years) of the interactive effects of twenty sessions of anodal tDCS over the left prefrontal cortex (vs. sham stimulation) and simultaneous working-memory training (vs. control training) on change in cognitive abilities. Stimulation did not modulate gains from pre to posttest on latent factors of either trained or untrained tasks in a statistically significant manner. A supporting meta-analysis (n=266), also including younger samples, showed that, when combined with training, tDCS was not much more effective than sham stimulation at changing working memory performance (g=0.07[-0.21-0.34]) and global cognition (g=-0.01[-0.29-0.26]) assessed off stimulation. These results question the general usefulness of current tDCS protocols for enhancing the effects of cognitive training on cognitive ability.